Corpos e beleza no Instagram: estetização em busca de likes - Silveira, Vanessa Rozan da (2017)
This research analyses the corporeal presence ways on Instagram social network and how this virtual platform provides to its users variations of body simulacra, considering their relationship to those who circulate in traditional media. Created in 2010, Instagram is a social network with the primary function of sharing photos and which brings together image editing capabilities, thus representing a convergence of cultural strengths: the digital documentation mania, the proliferation of celebrities and micro-celebrities and the conspicuous consumption. As study object, profiles of three women with a large number of followers were selected, representing different ways of staging the body and promoting identity construction values that have repercussions on followers and the media. They are: Kim Kardashian, Gabriela Pugliesi and Ashley Graham. Analyzing the photos published in their profiles of Instagram social network, from April to June 2016, we identified the themes that are materialized by figures reiterated by recurring themes, such as beauty, aesthetics and health, organizers of visual discourse. Thus, we present the way each profile builds its body simulacrum within this network and how they refer to seemingly subjective and predominantly objective presence modes. The investigation tested the hypotheses that (1). The changes in the beauty standards take place because this media allows each one the power to expose him/herself being his/her own destinator, in clear distinction to the strong destinator of the established media vehicles, that make bodies mediatic; 2. the advertising and fashion market takes advantage of these media independent body simulacra constructions and embraces them as new niches - once marginalized and currently with an active voice — by identifying them as business opportunities. We detected the plot of “luxury”, “being in fashion”, “being famous” and “thinness” values, materialized in the bodies analyzed in this research, which values are settled by women's magazines, the fashion market and advertising. We find that narrative paths of the social network Instagram shape their recipients to make images changes, and these subjects, bodies without artifice and bodies with devices, are shown by different mechanisms of visibility of the want-to-be seen order, in search of social sanction through followers “likes”. In this context, we found a greater propensity to align with bodies simulacrum and values already put into circulation in the publishing and advertising market, being these two strong contributors and developers of the taste for appearance, through fashion and consumption. The theoretical apparatus used was the semiotic theory developed by Algirdas Julien Greimas, complemented by Eric Landowski’s social-semiotics, by the plastic semiotics of Jean-Marie Floch and by the researches on the dressed body plastics, fashion and identity of Ana Claudia de Oliveira and Kathia Castilho